A historical analysis of modern Japan's exclusively English-focused foreign language education policies. Issue 1 (1st April 2022) - Shimo, Etsuko
Abstract : This paper discusses foreign language education policies in the school system in the Meiji (1868–1912) and Taisho (1912–1926) eras in Japan. The country's current exclusively English-focused policies in secondary school foreign language education were officially established with the enactment of the Middle School Teaching Rule Outline in 1881, in which English was listed as the only foreign language subject. German and French were added later, but their status was not as stable. In several policymaking-related meetings, such as the Upper-level Education Committee (1896–1913) and the Research Education Committee (1913–1917), exclusively English-focused foreign language education received criticism. However, the outcomes of meeting discussions always favoured English education. By examining discussions in the two committees and the Extraordinary Committee for Education (1917–1919), which succeeded those two, this paper notes that two factors contributed to the policy consequences: the purpose of foreign language education and the number of foreign languages for students to learn. The purpose of middle school education was prescribed as to provide male students with the most important higher-level general education and that of higher school education as to provide the complete achievement of higher-level general education. The purpose of foreign language education was not necessarily compatible with general education. Moreover, by adopting the One Foreign Language Principle, Japan's foreign language education inescapably became almost entirely English-focused to the detriment of other languages. The paper concludes by examining the assumptions that Japan's foreign language education policies have made about the Plural Foreign Language Principle.